"A Progression and a Regression at the Same Time": Hybrid Masculinities and Entrepreneurial Selfhood. Issue 2 (June 2017) - Whitmer, Jennifer M.
Research suggests normative masculinities are increasingly defined through consumption, particularly the consumption of fashions and cosmetics. Much existing research examines heterosexual men's reluctance to embrace consumer masculinities due to cultural associations, which associate consumption with femininities and subordinated masculinities. However, not all men are reluctant consumers. Little research has examined the relationship between masculinity and aesthetic consumption in a cultural context in which the body is increasingly framed as a tool for self-promotion and upward mobility. Drawing on qualitative research on male personal style bloggers, I examine the masculinities of men who actively turn the gaze on themselves, performing creative class ambitions through the display of the dressed body. I find privileged bloggers incorporate elements of non-hegemonic masculinities into the performance of hybrid masculinities, which allow them to distance themselves from the negative associations of hegemonic masculinity while continuing to reproduce sexual difference and hierarchies.